2004
DOI: 10.1148/radiol.2302021289
|View full text |Cite
|
Sign up to set email alerts
|

MR Image–based Grading of Lumbar Nerve Root Compromise due to Disk Herniation: Reliability Study with Surgical Correlation

Abstract: A system for grading lumbar nerve root compromise (no compromise, contact of disk material with nerve root, deviation of nerve root, and compression of nerve root) was tested in the interpretation of routine magnetic resonance images of 500 lumbar nerve roots in 250 symptomatic patients. Intra- and interobserver reliability was assessed for three independent observers. In the 94 nerve roots evaluated at surgery, surgical grading was correlated with image-based grading. kappa statistics indicated substantial ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
2
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 20 publications
1
146
2
8
Order By: Relevance
“…Women's higher symptom ratings can probably not be explained by pathoanatomical differences. An MRI study by Pfirrmann et al [29] found nerve root compromise equally distributed between the sexes, and Jensen et al [18] reported more nerve root compromise among men than in women. Our findings are in line with previous research showing that women show higher sensitivity to experimental pain [11,31] and report higher pain intensity than men in various clinical conditions [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Women's higher symptom ratings can probably not be explained by pathoanatomical differences. An MRI study by Pfirrmann et al [29] found nerve root compromise equally distributed between the sexes, and Jensen et al [18] reported more nerve root compromise among men than in women. Our findings are in line with previous research showing that women show higher sensitivity to experimental pain [11,31] and report higher pain intensity than men in various clinical conditions [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…All MRI assessments, clinical tests and self-reported outcomes have shown adequate reliability previously [1,11,18,26,28,29]. Thus, an inter-rater reliability evaluation was not performed in this study.…”
Section: Straight Leg Raising Test (Slr) a Validated Measure With A mentioning
confidence: 99%
“…MR images were analyzed by a well experienced radiologist (MA) using previously published classification systems [1,11,17,18]. The radiologist, who was blinded to all clinical information but the level of TESI, firstly, analyzed if DH existed, secondly, the type of DH (protrusion or extrusion), thirdly, the location of DH (central, subarticular, foraminal and extraforaminal) according to Fardon and Milette [19] and finally, the grade of nerve compression according to Pfirmann et al [1,11,18]. The subjects were classified as: no DH (n = 15), protrusion (n = 57) and extrusion (n = 27), and as: central (n = 15), subarticular (n = 45), foraminal (n = 18) and extraforaminal (n = 6) DH.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to nomenclature of North American Spine Society (NASS), the grading system of Pfirrmann and the physical examination rules for conscription in the Republic of Korea, which provide information on relations between the nerve root and the protruding disc, each of the four independent radiologists provided a grade from 1 to 5 by reviewing MRI, MRM, and myelography 7,16,17) . Grade 1 was regarded as minimal root irritation, indicating disc bulging or protrusion without root irritation.…”
Section: Radiological Factorsmentioning
confidence: 99%